Comparing High-Load Strength Training with Plantar-Specific Stretch and Manual Therapy for Plantar Fasciitis Pain (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2024)
Background: The plantar fascia, a substantial band of tissue running along the bottom of the foot from the heelbone to the toes, is involved in the inflammation and irritation of the condition. One in ten people will experienceplantar fasciitis at some point in their lives, making it a prevalent condition.Purpose: To compare the effectiveness of High-load strength training with plantar stretch and manual therapy onpain and functional recovery in subjects with plantar fasciitis.Materials and Methods: Thirty participants were randomly assigned to experimental (High-load strength trainingwith plantar stretch) and conventional (manual therapy) groups. The numerical pain rating scale (NPRS), and footand ankle ability measure (FAAM) were used to evaluate the pre-test. The same test was used to determine posttreatmentvalues after six weeks of treatment.Results: A significant difference was observed between the experimental and control groups (P =
Keywords: Plantar fasciitis, cross-friction massage, mobilization, high-load strength training exercise, plantar stretch.